2023
DOI: 10.1002/admi.202202139
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons in the Synthesis, Properties, and Applications of MXene Quantum Dots

Abstract: soum led the discovery of a new class of materials called MXene which was synthesized by selective etching of MAX phases. Here, a few layered arrays of (early) transition metal atoms are connected by a carbon/ nitrogen atom layer, linking the metallic layer known as transition metal carbides/nitrides or carbonitrides. [9,10] The general formula of MXene is M (n+1) X (n) T (x) or MAX; where M represents transition metal ions (such as Ti, Sc, Nb, and Mo), X represents Carbon or Nitrogen element, and T is any sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 157 publications
(328 reference statements)
0
6
0
Order By: Relevance
“…Changes in chemical and photophysical properties, such as increased surface area, quantum confinement, and edge effects, are also involved. So, the methods mentioned above are efficient for preparing MXene quantum dots by overcoming these challenges and further open a way for doping with different materials to enhance their properties. , …”
Section: Synthesis and Processing Of Ti3c2t X Mxenementioning
confidence: 99%
See 1 more Smart Citation
“…Changes in chemical and photophysical properties, such as increased surface area, quantum confinement, and edge effects, are also involved. So, the methods mentioned above are efficient for preparing MXene quantum dots by overcoming these challenges and further open a way for doping with different materials to enhance their properties. , …”
Section: Synthesis and Processing Of Ti3c2t X Mxenementioning
confidence: 99%
“…When comparing with layered Ti 3 C 2 T x MXene, Ti 3 C 2 T x QDs exhibit excellent optical properties attributed to quantum confinement effects. Also, Ti 3 C 2 T x QDs have a large specific surface area, tunable properties, and various hydrophilic functional groups . The Ti 3 C 2 MXene quantum dots (MQDs) were prepared by fluorine-free liquid exfoliation method, and they showed strong absorption in the NIR region with large extinction coefficients as high as 52.8 Lg –1 cm –1 .…”
Section: Optical Properties Of Ti3c2t X Mxenementioning
confidence: 99%
“…It further indicates the emergence of MXene QDs in a multifarious application. Applications of MXene and MXene-based nanomaterial in biosensing, biomedicine, bioimaging, and several other fields have been published. , Sinha et al described the emergence of MXenes, their electronic properties, surface functionalization techniques, and their application in biosensing application . The authors explained the role of MXene in development of different biosensors including electrochemical, piezoresistive, and photoluminescent sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also highlighted the importance of different synthesis methods and characterization techniques in the synthesis of high-performance MXene QDs. Other studies also reported the diverse forms of application of MXene QDs in energy conversion and storage devices, biosensing, biomedical applications, and environmental pollutant sensing. , Studies also provided descriptions of the synthesis process and modification strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as a new type of two-dimensional layered material, Ti 3 C 2 MXene has been widely used as a catalyst or co-catalyst due to its large surface area, high surface activity, and unique electrical and electrochemical properties. [27][28][29][30][31] Tian et al 32 developed the efficient and highly selective 1T-MoS 2 @Ti 3 C 2 for electrocatalytic nitrogen fixation, showing a FE of 10.94% and NH 3 yield of 30.33 μg h −1 mg −1 . Liu et al 33 utilized Cu/Ti 3 C 2 as a catalyst with a FE of 7.31% and an NH 3 yield of 3.04 μmol h −1 cm −2 .…”
mentioning
confidence: 99%